Beneficial Effect of Traditional Chinese Medicinal Formula Danggui-Shaoyao-San on Advanced Glycation End-Product-Mediated Renal Injury in Streptozotocin-Diabetic Rats. (7th August 2011) - Liu, I-Min; Tzeng, Thing-Fong; Liou, Shorong-Shii; Chang, Chia Ju
Abstract : The present study was undertaken to characterize the effects of Danggui-Shaoyao-San (DSS), a famous traditional Chinese medicine formula consisting of six herbal medicines, on diabetic nephropathy. Streptozotocin-induced diabetic rats were orally administrated DSS (2.8 g kg −1 per day) for 12 consecutive weeks. DSS partially decreased the high plasma glucose level in diabetic rats. Diabetic-dependent alterations in urinary albumin, 24-hour urinary albumin excretion rate, and creatinine clearance as well as the kidney hypertrophy (kidney weight/body weight ratio) and glomerular mesangial matrix expansion were ameliorated after 12 weeks of DSS treatment. The increased expression of nuclear factor- κ B as well as transforming growth factor- β 1 and the progressive accumulation of type IV collagen in kidney of diabetic rats were also attenuated by DSS. Not only the elevated levels of advanced glycation end products (AGEs) and N ε -(carboxymethyl)lysine but also the higher levels of lipid peroxidation products in kidney of diabetic rats were ameliorated by DSS. Decreased activity of superoxide diamutase and glutathione peroxidase in kidney of diabetic rats was enhanced by DSS. These data demonstrated that the renoprotective effects of DSS in STZ-diabetic rats not only were attributable to regulate plasma glucose to attenuate AGEs expression in diabetic glomeruli but also likely reflected its antioxidant activity.